Antibiofilm Effect of Clitoria ternatea Flower Juice on Porphyromonas gingivalis in vitro - Armelia Sari Widyarman; Stephani Sumadi; Tri Putriany Agustin (Indonesian Dental Association, 2018)
Introduction: Clitoria ternatea flower contains flavonoid such as anthocyanin that gives the blue color to its flower and has antimicrobial activity. Objectives: The aim of this study was to examine the effect of flower juice of Clitoria ternatea against Porphyromonas gingivalis biofilm viability in vitro. Methods: This study was experimental laboratory research using biofilm assay method. P. gingivalis was cultured in BHI broth in 37Â°C for 24h under anaerobic condition. Fresh flowers of Clitoria ternatea were extracted using mortar and pestle and diluted into 6 different concentrations: 100%, 50%, 25%, 12.5%, 6.25%, and 3.125% with phosphate buffer saline (PBS). Chlorhexidine (0.2%) was used as positive control and biofilm without treatment as negative control. The flower juice was distributed into 96 well-plates that contained biofilm of P. gingivalis and incubated for 1h, 3h, 6h, and 24h in 37Â°C, anaerobic atmosphere. Biofilm was measured using crystal violet dye with microplate reader (490 nm). Data were statistically analysed using one-way ANOVA test and Post Hoc test with p<0.05 was set as significant different. Result: Result showed that Clitoria ternatea flower juice significantly reduced the Porphyromonas gingivalis biofilm viability in all concentration and all incubation time. The most effective concentration to inhibit Porphyromonas gingivalis biofilm was 100% in 1h incubation time which biofilm was diminished (Optical Density=0.00). One way ANOVA test and Post Hoc test showed a significant biofilm reduction in all concentration and all incubation time after treatment with the flower juice compared to control (p<0.05). Conclusion: Clitoria ternatea flower juice has antibiofilm effect against Porphyromonas gingivalis. This result showed this flower juice may be useful for combating periodontal pathogens. However, further studies using other bacteria are still needed to confirm this result.